Effects of Exercise on Inflammatory Biomarkers in Rheumatoid Arthritis - Dusiel, Julia; Wałachowska, Anna; Tabian, Alicja; Kozłowska, Paulina; Smęt, Jakub; Chojnacka, Aleksandra Beata; Borawski, Jacek; Burdon-Sajnóg, Julia; Szymona-Kuciewicz, Zofia; Bartela, Klaudia Katarzyna (Journal of Education, Health and Sport, 2026)
Background Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by persistent synovial inflammation leading to joint destruction, disability, and increased cardiovascular risk. Exercise is increasingly recognized as a non-pharmacological therapy that may modulate inflammation and improve clinical outcomes in RA. Aim The aim of this review was to evaluate the effects of different exercise modalities on inflammatory biomarkers in individuals with RA. Material and methods A narrative review was conducted using studies published in peer-reviewed journals, identified through databases such as PubMed. Randomized controlled trials, clinical interventions, and systematic reviews assessing the impact of aerobic, resistance, and combined training on inflammatory markers in adults with RA were included. Data were extracted on exercise protocols, biomarker outcomes, and methodological quality. Results: Exercise interventions in RA show variable effects on inflammatory biomarkers. Aerobic training consistently reduces CRP and TNF-α, while effects on IL-6 and ESR are less consistent. Resistance training primarily lowers ESR and CRP, with transient changes in interleukins. Combined aerobic and resistance programs demonstrate the broadest anti-inflammatory impact, reducing CRP and IL-6, modulating regulatory T and B cells, and improving disease activity and quality of life. Short-term, moderate-intensity, and home-based interventions are safe and effective, whereas low-intensity exercise shows limited biomarker changes. Conclusions: Regular exercise is safe and beneficial for patients with RA, reducing disease activity, improving physical function, and modulating inflammatory biomarkers, particularly CRP and IL-6. Combined aerobic and resistance training offers the broadest anti-inflammatory and clinical benefits. Further research is needed to determine the most effective interventions for targeted modulation of inflammation.